Prediction of energy performance of an office Building through combined energy simulation and Computational fluid dynamics - Bandara, R.M.P.S.; Attalage, R.A.; Vignarajah, M. (University of Jaffna, 2015)
At present, high emphasize is given for designing energy efficient buildings in order to reduce their energy consumption and to limit the carbon footprint on the local and global environment. Energy Simulation is the most popular method in predicting the energy performance of buildings during the conceptual stage. However, it is observed that Energy Simulation tools show certain inherent deficiencies in predicting the energy performance of buildings. The said tools do not have the capacity to model air circulation through the building space explicitly. Energy Simulation tools mainly rely on the simplifying assumption that air within a thermal zone of a building is well mixed. Furthermore, convective heat transfer coefficients of building surfaces are calculated using set empirical correlations. The literature also reveals that most Energy Simulation tools under-predict energy consumption in buildings, especially located in tropical regions. On the other hand, Computational Fluid Dynamics tools are capable of predicting the indoor flow field comprehensively. On this basis, the paper explains how Energy Simulation can be coupled with Computational Fluid Dynamics in predicting the energy performance of a building more accurately through complementary data exchange between the tools. The office building considered in the study is to be constructed in the suburbs of Colombo. The analysis uses EnergyPlus 8.0 and Ansys Fluent 6.3 as the tools for conducting Energy Simulation and Computational Fluid Dynamics respectively. The study shows that the coupled scheme predicts a considerably higher annual energy consumption of the building compared to that given by conventional Energy Simulation using EnergyPlus.
Keywords: Energy Performance; Energy simulation; Computational fluid dynamics